Portable astronomical observation system based on large-aperture concentric-ring metalens - Jianli Wang; Yongting Deng; Chengmiao Wang; Yu Lin; Yeming Han; Junchi Liu; Xiufeng Liu; Hongwen Li; Jan G. Korvink; Yongbo Deng (Light: Science & Applications)
Abstract The core advantage of metalenses over traditional bulky lenses lies in their thin volume and lightweight. Nevertheless, as the application scenarios of metalenses extend to the macro-scale optical imaging field, a contradiction arises between the increasing demand for large-aperture metalenses and the synchronous rise in design and processing costs. In response to the application requirements of metalens with diameter reaching the order of 104 λ or even 105 λ, this paper proposes a novel design method for fixed-height concentric-ring metalenses, wherein, under the constraints of the processing technology, a subwavelength 2D building unit library is constructed based on different topological structures, and the overall cross-section of the metalens is assembled. Compared to global structural optimization, this approach reduces computational resources and time consumption by several orders of magnitude while maintaining nearly identical focusing efficiency. As a result, a concentric-ring metalens with a designed wavelength of 632.8 nm and a diameter of 46.8 mm was developed, and a quasi-telecentric telescope system composed of aperture stop and metalens was constructed, achieving high-resolution detection within a 20° field of view. In the subsequent experiments, the unique weak polarization dependence and narrowband adaptability of the meta-camera are quantitatively analyzed and tested, and excellent imaging results were finally obtained. Our work not only ensures the narrowband optical performance but also promotes the simplicity and light weight of the metalens based telescopic system, which further advances the deep application of large-diameter metalenses in the field of astronomical observation.